Apigenin inhibits epithelial-mesenchymal transition of human colon cancer cells through NF-κB/Snail signaling pathway. Issue 5 (14th May 2019) - Tong, Jiafeng; Shen, Ying; Zhang, Zhenghua; Hu, Ye; Zhang, Xu; Han, Li
Abstract : Colon cancer is a leading cause of cancer-related deaths worldwide. The epithelial-mesenchymal transition (EMT) plays an important role in tumor metastasis of colon cancer. We first evaluated the effects of EMT-related transcription factors on the prognosis of colon cancer through analysis the data obtained from The Cancer Genome Atlas (TCGA). And then we screened a series of Chinese medicine monomers to find effect EMT inhibitors. First, Snail is a more important EMT transcription factors for colon cancer prognosis, compared with Twist and Slug. Then, we found that apigenin effectively inhibits the activity of Snail. Apigenin could inhibit the EMT, migration, and invasion of human colon cancer cells in vitro and in vivo through the NF-κB/Snail pathway. Snail is a key regulator of EMT in colon cancer and Snail inhibitor apigenin may be a therapeutic application for patients with colon cancer.